An Upper Carboniferous trigonotarbid, Aphantomartus pustulatus (Scudder, 1884), from the Maritimes Basin (Euramerican Coal Province), New Brunswick, Canada - Miller, R.; Forbes, W. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2001)
A specimen of an aphantomartid trigonotarbid arachnid. Aphantomartus pustulatus (Scudder, 1884), found in the Upper Carboniferous (Westphalian C. Minio Formation) coalfields of New Brunswick, Canada, is only the second North American localily for this species Trigonotarbids are uncommon fossils in Carboniferous deposits, most described specimens being found in Europe Recent revision of the family Aphantomartidae identified only one genus with two species, which range from the Lower Carboniferous (Visean) lo the Lower Permian (Assclian). The specimen is the only aphantomartid trigonotarbid described from the Maritimes Basin of the Kuramencan Coal Province.